Exploring the Verb Agreement System in the Lohorung Language - Rai, Diwas (Journal of Indigenous Knowledge and Practice, 2025)
This article analyzes the verb agreement system in Lohorung, a Kirat Rai language belonging to the Tibeto-Burman family. Using elicitation methods with a native speaker and textual analysis, we find that Lohorung verbs exhibit simultaneous agreement with both subject and object pronouns, marked by , , , , and . The key findings reveal that: (a) present tense verbs with unmarked ergative subjects show single agreement, (b) clusivity is marked exclusively (inclusive forms remain unmarked), and (c) agreement undergoes assimilation (e.g., portmanteau for third person singular past. Notably, the system does not show gender or honorific distinctions. These results demonstrate Lohorung's complex yet rule-governed agreement morphology, contributing to Tibeto-Burman typology and endangered language documentation.